11. Missed Vaccine Opportunities During the COVID-19 Pandemic. (31st December 2020) - Shallal, Anita; Vahia, Amit T; Kenney, Rachel; Weinmann, Allison J
Abstract: Background: The 23-valent pneumococcal polysaccharide vaccine (PPSV23) is recommended for all adults over the age of 65 to reduce S. pneumoniae pneumonia. Our institution follows a standing order for nurses to vaccinate adults who meet the Advisory Committee on Immunization Practices (ACIP) criteria. During the COVID-19 pandemic surge, the pneumococcal vaccine and influenza vaccine nurse-driven protocol was determined to be non-essential on 3/23, and 4/2 respectively. Our study aims to characterize missed vaccine opportunities among patients hospitalized with COVID-19 during this surge. Methods: A retrospective cross-sectional study of PCR-positive COVID-19 patients admitted to an inner-city hospital and discharged alive between the dates of 3/23 and 4/21/2020. Patients under the age of 65 were excluded. Data collected included patient age, gender, race, length of stay, co-morbidities that would indicate a vaccine opportunity, prior vaccinations, and whether there was a vaccine opportunity for PPSV23 and influenza defined by ACIP indications. Vaccine history was evaluated using the electronic medical record (EMR) and Michigan Care Improvement Registry. If there was a vaccine opportunity, we documented whether a vaccine was given before hospital discharge. Total numbers of vaccines given for time periods in 2019 and 2020 were collected from EMR for comparison. Results: 100 patients over the age of 65 were included. The average age was 72.8 years, and most patients (66%) were of African American race. The mean length of stay was five days. 52 patients were identified as having an opportunity to receive PPSV23, and 0 patients received the vaccine. 67.3% had more than one indication for PPSV23. 37 patients were eligible to receive influenza vaccine, and 0 received the vaccine. Results are summarized in table 1. Figures 1 and 2 display the number of pneumococcal and influenza vaccines given per EMR, respectively. Figure 1 Figure 2 Table 1 Conclusion: Due to prioritization of potential staffing shortages and clustering nursing care, an opportunity to vaccinate patients with pneumococcal and influenza vaccines was missed. It is important for health care providers to be aware of this potential opportunity for vaccination of high-risk patients in order to promote primary prevention in future waves of pandemics. Disclosures: All Authors : No reported disclosures